Modeling and analysis performance of BLDC motor electric bicycle - Mohd Fadzli Shah, Ahmad Hamim (2016)
This project is about modeling and analysis of the technical performance of BLDC motor for e-bike whereas it will discuss about the modelling of a direct drive BLDC motor electric bicycle drive system for technical performance evaluation. A hardware called Cycle Analyst had been use to investigate the instantaneous drive parameters such as voltage, current, power and speed of the electric bicycle. The Cycle Analyst V3 measures and displays information about the battery, acts as a general-purpose trip computer, records and calculates vehicle and rider performance statistics, monitors and displays data from optional input devices, and operates or limits the mo-tor controller based on the monitored and calculated data. The Cycle Analyst come from different manufacturer of the controller set. In this project, its need to integrate with the existing controller of the electric bicycle. Besides, a simulation of rider performance from usual bicycle will be shown by using software called AnyBody.